Comparison of the Effects of Glucose and Fructose on Exercise Metabolism, Perceived Exertion, and Recovery in Untrained Females. (18th February 2014) - Folarin, Babatunde O.; Macdonald, Ian A.; Khaled, Latif; Jill, Patterson; Hannah, Capocci; Phil, Thirkell; Joy, Macdermid C.
Abstract : This double-blinded, crossover randomized controlled trial study was designed to establish if combined ingestion of glucose and fructose (GLU + FRU) at the moderate rate 0.5 g·min −1 would result in higher rates of carbohydrate (CHO) oxidation compared with glucose (GLU) alone. Eight untrained females (VO2max : 25.8 ± 3.2 mL·kg −1 ·min −1 ) cycled on two different occasions for 60 min at 50% of maximal power output (60% ± 1 % VO2max ) and consumed 12% CHO solution of either providing 0.33 g·min −1 glucose + 0.17 g·min −1 fructose (GLU + FRUC) or 0.5 g·min −1 of glucose (GLU) alone. Heart rate (HR) and rate of perceived exertion (RPE) were assessed during exercise and subjective exercise experience assessed two days after each trial. CHO oxidation was not significantly different (P > 0.05 ) between GLU + FRU and GLU (0.8 ± 0.06 g·min −1 and 0.78 ± 0.05 g·min −1, resp.). CHO oxidation rates during the final 30 min of the recovery period were not significantly different between GLU + FRU and GLU (0.17 ± 0.04 g·min −1 and 0.14 ± 0.05 g·min −1, resp.). Experience of distress was significantly higher (P < 0.05 ) for GLU compared to GLU + FRU. The results reveal that consuming modest amounts of glucose plus fructose does not boost CHO oxidation above that of glucose alone during submaximal exercise.